Consumption volatility risk and the inversion of the yield curve - Adriana Grasso; Filippo Natoli (European Central Bank (ECB), 2018)
We propose a consumption-based model that allows for an inverted term structure of real and nominal risk-free rates. In our framework the agent is subject to time-varying macroeconomic risk and interest rates at all maturities depend on her risk perception which shape saving propensities over time. In bad times, when risk is perceived to be higher in the short- than the long-term, the agent would prefer to hedge against low realizations of consumption in the near future by investing in long-term securities. This determines, in equilibrium, the inversion of the yield curve. Pricing time-varying consumption volatility risk is essential for obtaining the inversion of the real curve and allows to price the average level and slope of the nominal one.
Keywords: G12; 330; real rates; uncertainty; habits; inverted yield curve; volatility risk